Detailed analysis of failure patterns using deformable image registration in hypopharyngeal cancer patients treated with sequential boost intensity‐modulated radiotherapy. Issue 1 (14th November 2022) - Otsuka, Manami; Yasuda, Koichi; Uchinami, Yusuke; Tsushima, Nayuta; Suzuki, Takayoshi; Kano, Satoshi; Suzuki, Ryusuke; Miyamoto, Naoki; Minatogawa, Hideki; Dekura, Yasuhiro; Mori, Takashi; Nishioka, Kentaro; et al.
Abstract: Introduction: Sequential boost intensity‐modulated radiotherapy (SQB‐IMRT) uses two different planning CTs (pCTs) and treatment plans. SQB‐IMRT is a form of adaptive radiotherapy that allows for responses to changes in the shape of the tumour and organs at risk (OAR). On the other hand, dose accumulation with the two plans can be difficult to evaluate. The purpose of this study was to analyse patterns of loco‐regional failure using deformable image registration (DIR) in hypopharyngeal cancer patients treated with SQB‐IMRT. Methods: Between 2013 and 2019, 102 patients with hypopharyngeal cancer were treated with definitive SQB‐IMRT at our institution. Dose accumulation with the 1st and 2nd plans was performed, and the dose to the loco‐regional recurrent tumour volume was calculated using the DIR workflow. Failure was classified as follows: (i) in‐field (≥95% of the recurrent tumour volume received 95% of the prescribed dose); (ii) marginal (20–95%); or (iii) out‐of‐field (<20%). Results: After a median follow‐up period of 25 months, loco‐regional failure occurred in 34 patients. Dose–volume histogram analysis showed that all loco‐regional failures occurred in the field within 95% of the prescribed dose, with no marginal or out‐of‐field recurrences observed. Conclusion: The dosimetric analysis using DIR showed that all loco‐regional failures were within the high‐dose region. More aggressive treatment may be required for gross tumours.